Maternal and neonatal outcome of asymptomatic bacteriuria at term pregnancy. Issue 5 (7th September 2019) - Perlitz, Yuri; Saffoury, Enas; Shabso, Nora; Labai, Aminat; Namatiyof, Jennifer Fathy; Nitzan, Orna; Ben-Shlomo, Izhar; Azrad, Maya; Ben-Ami, Moshe; Peretz, Avi
ABSTRACT: Objectives: Guidelines recommend antibiotic treatment for every episode of asymptomatic bacteriuria throughout pregnancy in order to reduce maternal and fetal complications. We evaluated intra- and post-partum, as well as puerperal maternal and neonatal outcomes of an untreated group of pregnant women with asymptomatic bacteriuria at term. Methods: This was a single center prospective cohort study. We enrolled women who came for labor or checkups, 37–42 weeks gestation, with singleton, vertex presentation. On admission, women gave a urine sample; we compared maternal, obstetric and neonatal data from the positive culture group to the negative culture. Results: Among 248 pregnant women recruited, 205 negative and 32 positive urine cultures were collected. None of the women that participated in this study developed pyelonephritis during hospitalization or during the puerperium. No significant differences were detected between the two groups in terms of age, nulliparity, gestational age at delivery, length of hospitalization, birth type, intra- or post-partum fever, antibiotic treatment during labor or post-partum. Conclusions: No increased maternal or neonatal adverse effects were observed in women with untreated ASB detected at term. Abstract : There is no need to obtain a routine urine culture from asymptomatic women at term. If taken and asymptomatic bacteriuria is diagnosed, there might be no benefit in treating this infection.